Tsunamis from the 29 March and 5 May 2015 Papua New Guinea earthquake doublet (Mw 7.5) and tsunamigenic potential of the New Britain trench. Issue 14 (30th July 2015) - Heidarzadeh, Mohammad; Gusman, Aditya Riadi; Harada, Tomoya; Satake, Kenji
Abstract: We characterized tsunamis from the 29 March and 5 May 2015 Kokopo, Papua New Guinea, Mw 7.5 earthquake doublet. Teleseismic body wave inversions using various rupture velocities ( Vr ) showed similar source‐time functions and waveform agreements, but the spatial distributions of the slips were different. The rupture durations were ~45 and ~55 s for the March and May events, with their peaks at ~25 and at ~17 s, respectively. Tsunami simulations favored source models with Vr  = 1.75 and 1.50 km/s for the March and May earthquakes. The largest slip on the fault was similar (2.1 and 1.7 m), but the different depths and locations yielded maximum seafloor uplift of ~0.4 and ~0.2 m. Tsunami simulation from hypothetical great earthquakes ( M 8.4 and 8.5) on the New Britain trench showed that tsunami amplitudes may reach up to 10 m in Rabaul, but most tsunami energy was confined within the Solomon Sea. Key Points: First instrumentally recorded tsunamis in the New Britain trench Slow rupture velocities estimated from seismic and tsunami analyses Different tsunamis in earthquake doublet due to different location and depth